Food oral processing : fundamentals of eating and sensory perception - Chen, Jianshe, 1961-; Engelen, Lina (Chichester, West Sussex, UK ; Ames, Iowa : Wiley Blackwell, A John Wiley & Sons, Ltd., Publication, 2012)
This volume provides an overview of the latest research findings on the physics, physiology, and psychology of food oral consumption, as well as the experimental techniques available for food oral studies. Coverage includes the main physical and physiological functionalities of the mouth; the location and functionalities of various oral receptors; the main sequences of eating and drinking, and the concomitant food disintegration and destabilisation. Chapters also explain oral processing and its relation to flavour release and texture perception, and there is an introduction to the principles of food rheology as they relate to eating. Food Oral Processing is directed at food scientists and technologists in industry and academia, especially those involved in sensory science and new product development. It will also be of interest to oral physiologists, oral biologists and dentists. The book will be a useful reference for undergraduate and postgraduate students of these disciplines.
Oral anatomy and physiology -- Oral cavity -- Oral receptors -- Role of saliva in the oral processing of food -- Food oral management -- Oral management of food -- Breaking and mastication of solid foods -- Oral behaviour of food emulsions -- Bolus formation and swallowing -- Food oral processing and sensory perception -- Oral processing and texture perception -- Oral processing and flavour sensing mechanisms -- Multi-sensory integration and the psychophysics of flavour perception -- Principles and practices of instrumental characterisation for eating and sensory perception studies -- 'Oral' rheology -- 'Oral' tribology -- Applications of electromyography (EMG) technique for eating studies -- Soft machine mechanics and oral texture perception -- Applications and new product developments -- Appreciation of food crispness and new product development -- Design of food structure for enhanced oral experience.
Includes bibliographical references and index.
Online resource; title from electronic title page (ebrary, viewed on January 13, 2013).
Keywords: Ingestion; Drinking (Physiology); Food habits; Taste; Chemical engineering; Engineering; MEDICAL -- Nutrition; Drinking (Physiology); Food habits; Ingestion; Taste; Eating -- physiology; Drinking -- physiology; Feeding Behavior; Taste Perception -- physiology; Electronic books